Parkinson's disease, genetic variability and the Faroe Islands. Issue 1 (January 2015) - Petersen, Maria Skaalum; Guella, Ilaria; Bech, Sara; Gustavsson, Emil; Farrer, Matthew J.
Abstract: Introduction: The Faroe Islands is a geographically isolated population in the North Atlantic with a high prevalence of Parkinson disease (PD). The disease etiology is still unknown, although dietary pollutants are considered a risk factor. The genetic risk underlying disease susceptibility has yet to be elucidated. Methods: Sequence analysis was performed in genes previously linked with PD in 91 patients and 96 healthy control subjects. Results: Fourteen missense mutations, of which one was novel, were identified in six genes. One patient (1%) did carry the known pathogenic mutation LRRK2 p.G2019S mutation, 19 patients (22%) did carry mutations of unknown significance while 70 patients (78.0%) did not have any identifiable genetic risk. A total of 14 controls (14.6%) carried mutations of unknown significance. Conclusion: This study suggests that rare variants in genes previously linked to PD are not major contributors to PD in the Faroe Islands. Further exome sequencing and comparative analyses within and among well-described pedigrees with multi-incident PD are now warranted. Highlights: An isolate with a high prevalence of Parkinson disease. Sequence analysis identified 14 missense mutations. Genes linked with Parkinson's disease are not major contributors to PD in the Faroe Islands.